Dinamika Perubahan Sosial dalam Syndrom Hyperrealitas - Andi Egy Dirgantara (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2021)
Social change in general can be defined as a process of shifting or changing the structure/order in the society, include more innovative mindset, attitude, and social life in order to get a more dignified livelihood. The changes that occur in the community nowadays is normal symptoms. His influence could spread quickly to other parts of the world thanks to the presence of modern communication. New discoveries in the field of technology happens somewhere, it quickly can be known by other societies that are far away from the venue. Social change always brings out the dynamics that unwittingly connected with the reality of conflicts in society.